Biventricular impact of mild to moderate fetal pulmonary valve stenosis. (7th March 2018) - Guirado, L.; Crispi, F.; Masoller, N.; Bennasar, M.; Marimon, E.; Carretero, J.; Gratacós, E.; Martínez, J. M.; Friedberg, M. K.; Gómez, O.
ABSTRACT: Objectives: To define the pattern of fetal echocardiographic changes associated with isolated pulmonary valve stenosis (PS) and to correlate the echocardiographic findings with neonatal outcome and the need for postnatal pulmonary valvuloplasty within the first 12 months postpartum. Methods: This was a prospective cohort study between January 2009 and October 2015 of 16 fetuses with isolated PS and 48 controls matched by gestational age at ultrasound examination (± 2 weeks) evaluated at the Fetal Cardiology Unit at BCNatal (Barcelona). Standard fetal ultrasound and comprehensive echocardiography, which included cardiovascular morphometric parameters, and systolic and diastolic functional and timing measurements, were performed in all cases. Baseline characteristics and perinatal outcome were retrieved from clinical records. Cases were followed up until 12 months of age, and admission to intensive care unit, days of hospitalization, need for prostaglandins and requirement for postnatal surgery were reviewed. Fetal PS cases were analyzed according to the need for postnatal pulmonary valvuloplasty. Results: The study groups were similar in terms of baseline, fetal ultrasound and perinatal characteristics. Median gestational age at diagnosis of PS was 33.4 (range, 20.0–36.5) weeks. Most cases corresponded to mild or moderate PS; only three fetuses had reversed flow in the ductus arteriosus before delivery. Six (37.5%) newborns, including all three with reversed flow in the ductus arteriosus prenatally, required postnatal pulmonary valvuloplasty. Fetuses with PS presented with larger and more globular hearts, with increased myocardial wall thickness in the third trimester. Despite preserved right ventricular (RV) ejection fraction and systolic longitudinal motion, PS cases showed increased right cardiac output and signs of diastolic dysfunction, with higher ductus venosus pulsatility index (0.72 ± 0.32 vs 0.53 ± 0.16, P  = 0.004) and tricuspid E/E′ ratio (7.52 ± 3.07 vs 5.76 ± 1.79, P  = 0.022). In addition, fetuses with PS displayed a compensatory increase in left ventricular (LV) radial and longitudinal motion, as shown by a higher ejection fraction (79.3 ± 8.23% vs 67.6 ± 11.3%, P  = 0.003) and mitral annular‐plane systolic excursion (5.94 ± 1.38 vs 5.0 ± 1.22 mm, P  = 0.035). Finally, fetuses requiring postnatal pulmonary valvuloplasty showed a different pattern of echocardiographic findings from those not requiring valvuloplasty, with a significantly smaller RV and pulmonary valve diameter, reduced tricuspid annular‐plane systolic excursion (5.08 ± 1.59 vs 8.07 ± 1.93 mm, P  = 0.028), increased LV cardiac output (340 ± 16 vs 176 ± 44 mL/min/kg, P =  0.003) and more pronounced signs of LV diastolic dysfunction (mitral E′ velocity, 5.78 ± 0.90 vs 8.16 ± 1.58 cm/s, P  = 0.008). Conclusions: Fetuses with PS present with more hypertrophic, larger and more globular hearts in the third trimester of pregnancy, associated with a higher right cardiac output and impaired biventricular relaxation. In addition, signs of increased LV contraction were observed. Our data suggest that RV and LV functional parameters could be useful for predicting the need for postnatal pulmonary valvuloplasty. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.